THE EFFECT OF SERVICE MARKETING MIX ON THE DECISION TO USE THE SERVICE OF GARUDA INDONESIA AIRLINES IN PALEMBANG - Fredy Aranda Kunadi; Islahuddin Daud; Ahmad Nazarudin (JEMBATAN, 2015)
This study aims to determine the effect of service marketing mix consist of product in the form of service, price, promotion, place/distribution, people, physical environment, process and productivity and the quality of the decision to use the services of Garuda Indonesia in Palembang. Respondents in this study are 90 of Garuda Indonesian consumers in Palembang whom at least using Garuda Indonesia flight services in Palembang for 2 times and aged at 17 years or above. The analysis technique used in this study is multiple linear regression analysis and regression equation coefficients test. The results shows that the service marketing mix simultaneously affect the decision to use the services of Garuda Indonesia Airlines in Palembang. In partial, promotion, physical environment as well as productivity and quality affect the decision to use the services of Garuda Indonesia Airlines in Palembang. Product, price, place, people, and processes have no partial effect on the decision to use the services of Garuda Indonesia Airlines in Palembang.Keywords: Service Marketing Mix, 8P, Purchasing Decision